Publishing educational materials in Africa 2 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Publishing educational materials in AfricaThe economics of publishing educational materials in Africa draws on research data from a wide range of African countries. It examines the vital relationship between educational policy makers and educational...